MALDI-TOF-Based Affinity Selection Mass Spectrometry for Automated Screening of Protein–Ligand Interactions at High Throughput. (January 2021) - Simon, Roman P.; Winter, Martin; Kleiner, Carola; Wehrle, Lucie; Karnath, Michael; Ries, Robert; Zeeb, Markus; Schnapp, Gisela; Fiegen, Dennis; Häbe, Tim T.; Runge, Frank; Bretschneider, Tom; et al.
Demonstration of in vitro target engagement for small-molecule ligands by measuring binding to a molecular target is an established approach in early drug discovery and a pivotal step in high-throughput screening (HTS)-based compound triaging. We describe the setup, evaluation, and application of a ligand binding assay platform combining automated affinity selection (AS)-based sample preparation and label-free matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) analysis. The platform enables mass spectrometry (MS)-based HTS for small-molecule target interactions from single-compound incubation mixtures and is embedded into a regular assay automation environment. Efficient separation of target–ligand complexes is achieved by in-plate size exclusion chromatography (SEC), and small-molecule ligands are subsequently identified by MALDI-TOF analysis. In contrast to alternative HTS-capable binding assay formats, MALDI-TOF AS-MS is capable of identifying orthosteric and allosteric ligands, as shown for the model system protein tyrosine phosphatase 1B (PTP1B), irrespective of protein function. Furthermore, determining relative binding affinities (RBAs) enabled ligand ranking in accordance with functional inhibition and reference data for PTP1B and a number of diverse protein targets. Finally, we present a validation screen of more than 23, 000 compounds within 24 h, demonstrating the general applicability of the platform for the HTS-compatible assessment of protein–ligand interactions.